Risk Perception and Perceived Effects on Environment vis-à-vis Dairy Animal Waste Management in NCR, India - M. Madhavan , Misha; Sankhala, Gopal; Maiti, Sanjit; S. Smitha,; Chandrakumar, Aswathy (Indian Journal of Extension Education, 2024)
The study was carried out to evaluate the risk perception and perceived effect on the environment among dairy farmers in the National Capital Region (NCR) of India. The study conducted in seven districts across four sub-regions of NCR during 2018-19 included the development of a psychometric scale with four dimensions and standardization to measure risk perception. The scale was then administered to 252 dairy farmers from urban and peri-urban dairies in the study area. The results showed that the majority of the farmers perceived a medium level of risk (39.68%), followed by low (32.54%) and high (27.78%) levels of risk perception. Comparative analysis was conducted using Mann-Whitney U Statistic and Duncan Multiple Range Test, which found that the risk perception scores of the respondents in urban areas were significantly higher than those in peri-urban areas. The dairy farmers in the Delhi region of NCR perceived more risk with a mean value of 46.83+0.70, followed by Haryana (43.46+0.58), Uttar Pradesh (31.47+0.49), and Rajasthan (29.44+0.59). The use of dairy animal waste as manure in crop fields was ranked first among the positive effects, while the emission of greenhouse gases was recognized as the major negative effect perceived by farmers.